Chromium isotope fractionations resulting from electroplating, chromating and anodizing: Implications for groundwater pollution studies. (May 2017) - Novak, Martin; Chrastny, Vladislav; Sebek, Ondrej; Martinkova, Eva; Prechova, Eva; Curik, Jan; Veselovsky, Frantisek; Stepanova, Marketa; Dousova, Barbora; Buzek, Frantisek; Farkas, Juraj; Andronikov, Alexandre; et al.
Abstract: A number of shallow aquifers in industrial regions have been polluted by toxic Cr(VI). At some sites, spontaneous reduction of dissolved Cr(VI) to insoluble Cr(III) has been observed. Precipitation of non-toxic Cr(III) is accompanied by a Cr isotope fractionation, with the residual Cr(VI) becoming enriched in the heavier isotope 53 Cr, and depleted in the lighter isotope 52 Cr. Thus far, δ 53 Cr values of the contamination source have been poorly constrained. These values are needed to quantify the extent of Cr(VI) reduction in the aquifers. We present δ 53 Cr values of solutions generated during Cr-electroplating, chromating and anodizing at nine industrial sites. The source chemical, CrO3, had a mean δ 53 Cr of 0.0‰. A small-to-negligible Cr isotope fractionation was observed between the solutions of the plating baths and the source chemical. Across all sample types, the mean δ 53 Cr(VI) value was 0.2‰. The mean δ 53 Cr(VI) value of contaminated groundwater in the same region, studied previously, was significantly higher (2.9‰), indicating Cr(VI) reduction. Based on low δ 53 Cr(VI) values of plating baths and rinsewaters as potential contamination sources, and their low variability, we suggest that most aquifer δ 53 Cr(VI) values higher than 1.0‰ are a result of in-situ Cr(VI) reduction. Highlights: δ 53 Cr(VI) of plating baths sampled at 9 industrial sites averages 0.2‰. Electroplating and chromating cause an extremely small Cr isotope fractionation. δ 53 Cr(VI) in aquifers >1‰ may indicate natural attenuation due to Cr(VI) reduction.